Peran Sekolah Islam Terpadu Dalam Mencegah Perilaku Bullying - Aurellia Nindya Tasya; Endah Tri Wahyuningsih (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE ROLE OF INTEGRATED ISLAMIC SCHOOLS IN PREVENTING BULLYING BEHAVIOR Bullying behavior is a serious problem in the world of education that can negatively impact the psychological, social, and academic development of students. Schools as formal educational environments have a strategic role in preventing such behavior, especially Integrated Islamic Schools that integrate Islamic values ​​​​in the entire learning process. This study aims to examine the role of Integrated Islamic Schools in preventing bullying behavior through a tawhid education approach, character-oriented learning of faith and morals, collaboration between teachers and parents, and the creation of a conducive and Islamic school environment. The research method used is a literature study by reviewing various national journals accredited by SINTA 4 that are relevant to the research topic. Data analysis was conducted using a descriptive-reflective approach to understand and synthesize the findings of previous studies. The results of the study indicate that tawhid education plays a role in the formation of moral awareness and self-control in students, thereby preventing deviant behavior such as bullying. Contextual and applicable learning of faith and morals has proven effective in instilling the values ​​​​of empathy, responsibility, and social concern. Furthermore, strong synergy between teachers and parents, as well as a safe and Islamic-inspired school environment, significantly contribute to creating a school culture free from bullying. Therefore, the implementation of comprehensive Islamic education in Integrated Islamic Schools is a crucial strategy for sustainable bullying prevention.